2015
DOI: 10.1002/rra.2918
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modelling of Braided Rivers with Structure‐from‐Motion‐Derived Terrain Models

Abstract: The development of three‐dimensional reconstructions of channel morphology has historically been limited by the high costs of geospatial data collection and software modelling. Advances in image processing, sensor technology and portable remote‐sensing platforms, however, now offer the opportunity to derive survey quality terrain models at significantly reduced cost and without traditional deployment and logistical constraints. There is a pressing need to establish whether new geospatial technologies such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
1
34
0
1
Order By: Relevance
“…Javernick et al. () showed similar results using Delft3D in 2D mode for braided river floodplains, where simulated and observed inundation patterns achieved a maximum of 81% agreement, and modeled depth errors were comparable to DEM uncertainty.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Javernick et al. () showed similar results using Delft3D in 2D mode for braided river floodplains, where simulated and observed inundation patterns achieved a maximum of 81% agreement, and modeled depth errors were comparable to DEM uncertainty.…”
Section: Resultsmentioning
confidence: 69%
“…The last two issues could be important in these floodplain wetland environments where interactions with vegetation and groundwater can be difficult to model (Javernick et al. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To reliably characterize such diversity in dynamic fluvial systems, objective, accurate, and efficient methods are needed (Woodget, Visser, Maddock, & Carbonneau, 2016). In particular, the combined approach of digital photogrammetry techniques and small unmanned aerial vehicle (UAV)-based image capture has emerged as a valuable way to measure river channel topography in three dimensions (Fonstad, Dietrich, Courville, Jensen, & Carbonneau, 2013;Javernick, Brasington, & Caruso, 2014;Javernick, Hicks, Measures, Caruso, & Brasington, 2015;Vericat, Brasington, Wheaton, & Cowie, 2008;Woodget, Carbonneau, Visser, & Maddock, 2014). In particular, the combined approach of digital photogrammetry techniques and small unmanned aerial vehicle (UAV)-based image capture has emerged as a valuable way to measure river channel topography in three dimensions (Fonstad, Dietrich, Courville, Jensen, & Carbonneau, 2013;Javernick, Brasington, & Caruso, 2014;Javernick, Hicks, Measures, Caruso, & Brasington, 2015;Vericat, Brasington, Wheaton, & Cowie, 2008;Woodget, Carbonneau, Visser, & Maddock, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of researchers have found that a metric resolution is needed to reasonably approximate hydraulic habitat, i.e., local depth and velocity, which is relevant to river ecology and morphology (Crowder and Diplas, 2000;Cook and Merwade, 2009;Clifford et al, 2010;Williams et al, 2013;Abu-Aly et al, 2014). Furthermore, with the aid of analytical models for the vertical velocity distribution including a characterization of bed roughness, metric-resolution 2D models can reconstruct a 3D characterization of flow for a wide range of applications at far less computational expense than 3D models based on the Navier-Stokes equations (Begnudelli et al, 2010;Abu-Aly et al, 2014;Wyrick et al, 2014), although there are many examples of 3D flow phenomena that demand 3D models for an accurate description such as horseshoe vortices around bridge piers and similarly complex turbulent velocity fluctuations occurring around boulders, large bed forms, and other types of flow obstructions (Wu, 2007;Javernick et al, 2015).…”
Section: Introductionmentioning
confidence: 99%